New entomopathogenic species in the Clavicipitaceae family (Hypocreales, Ascomycota) from the subtropical forests of Fujian, China - Lin, Longbing; Lin, Yongsheng; Keyhani, Nemat O.; Pu, Huili; Yang, Jiao; Xiong, Chengjie; Shang, Junya; Mao, Yuchen; Yang, Lixia; Zheng, Minghai; Zhu, Mengjia; Mu, Taichang; et al. (Frontiers in Microbiology, 2025)
IntroductionEntomopathogenic fungi play a crucial role in the ecological regulation of insect populations and can be exploited as a resource for pest control, sustainable agriculture, and natural products discovery. These fungi and their infected hosts are sometimes highly coveted as part of traditional medicine practices. Here, we sought to examine the biodiversity of entomogenous fungi in subtropical forests of China.MethodsFungal-infected insect specimens were collected from various sites in Fujian Province, China, and purified isolates were obtained through laboratory cultivation and isolation techniques. Molecular characterization of specific target genomic loci was performed on the fungal isolates, and used for phylogenetic analyses using Bayesian inference and maximum likelihood methods to elucidate their taxonomic relationships. Microscopy was used to describe the morphological features of the isolates.ResultsThrough a comprehensive two-year survey of Fujian Province via multilocus molecular phylogenetic analysis targeting the nrSSU, nrLSU, tef1-α, rpb1, and rpb2 loci of collected specimens, we identified three novel species within the Clavicipitaceae herein described as: Albacillium fuzhouense sp. nov., Conoideocrella gongyashanensis sp. nov. and Neoaraneomyces wuyishanensis sp. nov., as well as the recently recorded, Metarhizium cicadae. Each new species was also distinguished from its closest relatives by unique morphological characteristics.DiscussionThese discoveries enrich our understanding of biodiversity within the Clavicipitaceae family and can contribute to the development of new pest control strategies and natural products discovery.